Konstruksi Pembagian Peran Suami dan Istri dalam Hukum Keluarga Islam: Perspektif Teori Fungsionalisme Struktural - Jihan Al Layyinah; Heni Satar Nurhaida; Mushbihah Rodliyatun (Lembaga Yasin AlSys, 2026)
The division of roles between husband and wife in Islamic Family Law is a normative construction aimed at realizing a harmonious, prosperous, and sustainable family. Contemporary social changes, particularly the increasing participation of women in the public and economic sectors, have driven a transformation in relational patterns within Muslim families, so that the division of roles can no longer be understood rigidly. This study aims to analyze the construction of the division of roles between husband and wife in Islamic Family Law through the perspective of structural functionalism theory. This study used a normative legal method with a library research approach through a review of relevant legal sources and literature. The results showed that the division of roles between husband and wife has a social function in maintaining family stability, integration, and continuity, but this function does not have to be realized through fixed and hierarchical role patterns. Family stability is more determined by the success of husband and wife in carrying out family functions according to needs, public benefit, and the developing social context. The conclusion of this study affirms that the construction of role division in Muslim families needs to be understood functionally, namely by maintaining the fundamental goals and values of the family without closing the space for adaptation to social change. The contribution of this study lies in the development of the concept of functional flexibility, namely the understanding that what needs to be maintained in Muslim families is not a rigid form of role division, but rather the functions, goals, and public benefit to be achieved through that division of roles.